2008
DOI: 10.1086/533433
|View full text |Cite
|
Sign up to set email alerts
|

On the Weakening of the Chromospheric Magnetic Field in Active Regions

Abstract: Simultaneous measurement of line-of-sight (LOS) magnetic and velocity fields at the photosphere and chromosphere are presented. Fe I line at λ6569 and H α at λ6563 are used respectively for deriving the physical parameters at photospheric and chromospheric heights. The LOS magnetic field obtained through the centerof-gravity method show a linear relation between photospheric and chromospheric field for field strengths less than 700 G. But in strong field regions, the LOS magnetic field values derived from H α … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
2
7
1
Order By: Relevance
“…This inference recalls the publications where the photospheric and chromospheric magnetic fields were compared (Abramenko et al (1992), Choudhary et al (2002), Leka & Metcalf (2003), Balasubramaniam et al (2004); see also a resent review by Nagaraju et al (2008) and references in). Their results suggest that the stronger the line-of-sight magnetic field, the faster it decreases with height.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…This inference recalls the publications where the photospheric and chromospheric magnetic fields were compared (Abramenko et al (1992), Choudhary et al (2002), Leka & Metcalf (2003), Balasubramaniam et al (2004); see also a resent review by Nagaraju et al (2008) and references in). Their results suggest that the stronger the line-of-sight magnetic field, the faster it decreases with height.…”
Section: Discussionsupporting
confidence: 71%
“…Their results suggest that the stronger the line-of-sight magnetic field, the faster it decreases with height. Nagaraju et al (2008) argued that for the photospheric field stronger than 700 G, the chromospheric field values "are much weaker than what one gets from the linear relationship [between the photospheric and chromospheric fields] and also from those expected from the extrapolation of the photospheric magnetic field" in the potential approximation. Leka & Metcalf (2003) observed that the potential field of NOAA 8299 extrapolated from the photosphere to reasonable heights (lower than 2 Mm) statistically exceeds the observed chromospheric field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dual-beam polarimeters are becoming more and more popular among the astronomical community, such as the ones described by Packham et al (2005), Masiero et al (2008) and Nagaraju et al (2008). The high contrast ratios achieved by polarimetry make this technique a promising tool to characterize exoplanets as well as circumstellar environments.…”
Section: Resultsmentioning
confidence: 99%
“…Diagnosing chromospheric magnetic field 47 Inspite of its ubiquitous presence H α has been rarely used for probing chromospheric magnetic field. To mention a few, Abdusamatov & Karat (1971); Balasubramaniam et al (2004); Hanaoka (2005); Nagaraju et al (2008) have presented chromospheric magnetic field measurements through H α spectropolarimetry. One of the reasons for rarely using this line for magnetic field measurements is interpreting the observations is notoriously difficult.…”
Section: Introductionmentioning
confidence: 99%